Working memory and target-related distractor effects on visual search. - Balani, AB; Soto, D; Humphreys, G (2010)
We examined two forms of top-down effects on visual selection: (1) information held in working memory (WM) and (2) the semantic relations between targets and distractors. We found that items held in WM affected search for a different target. This WM-based interference effect generalized across different exemplars, even though participants could remember the specific exemplar on the trial. This argues against a memory top-up account of performance. In addition, there was interference from distractors that were not held in WM but were semantically related to the target. The effects of WM capture and the effects of capture by a distractor related to the target combined additively. The data suggest that task-irrelevant information in WM and task-relevant templates for targets compete separately for selection. The implications for understanding top-down processes in search are discussed.